Dwa listy z korespondencji między Erazmem Piltzem a Tomášem G. Masarykiem w sprawie sojuszu polsko-czechosłowackiego w 1925 r.Dwa listy z korespondencji między Erazmem Piltzem a Tomášem G. Masarykiem w sprawie sojuszu polsko-czechosłowackiego w 1925 - Dąbrowski, Dariusz (Fides, Ratio et Patria. Studia Toruńskie, 2015)
The years 1922–1925 was a period of seeking a compromise in the Polish-Czechoslovak relations. This was especially evident during the reign of two Polish foreign ministers Marian Seyda and Alexander Skrzyński. Their active emissary was Erasmus Piltz, the former deputy Polish in Czechoslovakia, a friend of many politicians, among others, of Tomáš G. Masaryk – the President of Czechoslovakia. The presented documents concern the correspondence between the two politicians. The economic cooperation and favorable international situation led to a rapprochement between the two countries, the result of which was a visit of Beneš in Warsaw on 19–23 April 1925. Contents then Conciliation and arbitration treaty, convention trade andan agreement on legal matters and commercial matters.The continuation of this policy was the return visit of Minister of Foreign Affairs Alexander Skrzyński in Prague, April 13–15, 1926.